Rindzevičiūtė: Power of Systems - Dayé, Christian (Serendipities. Journal for the Sociology and History of the Social Sciences, 2018)
Book review of: Rindzevičiūtė, Eglė. 2016. The Power of Systems: How Policy Sciences Opened Up the Cold War World. Ithaca, London: Cornell University Press, 2016. 306 pp. ISBN: 978-1-5017-0318-8 Price: $ 49.95